Study on digging form of mechanized harvesting of Cyperus esculentus and optimization test of device parameters - Xiaoning He; Shikuan Ma; Zhixin Liu; Shuqi Shang; Dongwei Wang (Scientific Reports)
Abstract This paper proposes an innovative back-rotating flinging method for digging out oilseed beans, which is more suitable for lifting the excavated material, in response to the short service life of the existing digging device caused by the entanglement of the root system with the cutting tool. Through the analysis of the interaction and influence between the rotary tiller and the soil-root complex of the plant, a kinetic model of the soil-root complex of the kudzu rhizome being chopped and thrown was constructed, and the operating mechanism of the reverse rotary tiller for the overall overturning, digging and collision fragmentation of the soil-root complex of the plant root system was clarified. A discrete element model of the soil-enveloped root system of the hyacinth bean plant was constructed in its entirety. The structural parameters of the reverse rotary digging device were optimised using discrete element simulation and field bench tests.